Open education licensing : effective open licensing policy and practice for Australian universities : final report. - Wright, Robin; Bossu, Carina; Padgett, Luke; Whitehead, Derek (Australia. Dept of Education, Skills and Employment, 2021)
Copyright and open licensing has been identified as one of the greatest challenges to the development and adoption of open educational practices (OEP) in Australia (Bossu, et al., 2014). Without clear information on open licensing for educational materials and its interaction with Australian copyright law, Australia’s higher education sector will be restricted in its ability to use, develop and distribute material such as open educational resources (OER) and massive open online courses (MOOCs) effectively or to be globally competitive in this market. This project aimed to address a critical need identified in previous Australian Government Office of Learning and Teaching projects: to review the copyright and legal issues affecting OEP and to improve Australia’s competitive strength in the international market for open education services by providing confidence for educational institutions around the development and production of open online resources. The project was undertaken jointly by Swinburne University of Technology and University of Tasmania. The project team included staff from both institutions with expertise in the application of copyright law in the higher education sector, research in learning and teaching and the use and development of OER. A survey was distributed through direct email to 389 individuals from 38 Australian universities and also through the electronic newsletters and bulletins of six key professional and industry bodies. During survey data collection, participants were asked whether they would be willing to participate in further discussion about the issues covered in the survey. Seven individuals were then selected for further follow-up interviews to provide a deeper understanding of issues explored through the survey, based on their responses and institutional affiliations. The interviews were recorded and transcribed for later analysis. Project findings from the survey and interviews informed the development of two key project deliverables: the OEL Toolkit and six case studies of OEP best practice in Australian universities. [Publisher summary, ed]